The Role of Teachers in Instilling Sedulur Sikep (Samin Tribe) Values in Early Childhood - Rosbiyarti, Ayu; Fadjryana Fitroh, Siti (Nak-Kanak: Journal of Child Research, 2024)
The role of a teacher is an indispensable aspect of the education world, particularly in fulfilling the national educational process standards. The teacher's role in promoting character education can be tailored to the cultural wisdom of a specific region. With the advancement of technology and changing times, the teacher's role in education may no longer appear as prominent. Consequently, teachers often carry out their duties without emphasizing their role as educators. This research employs a qualitative case study approach using Miles and Huberman's model. The findings of this study indicate that teachers function as guides and supervisors in the growth and development of children. They oversee the thoughts, words, and behaviors of both students and themselves, monitor the assessment results, and work on improving the behaviors, thoughts, and words of both students and teachers. The implementation of Sedulur Sikep character teachings by teachers involves three core character teachings: (a) "Angger-angger pratikel" (ethical behavior): Encouraging honesty in everyday life and teaching students not to harbor jealousy or greed towards their peers. (b) "Angger-angger pangucap" (language usage): Promoting the use of Javanese Krama Inggil when communicating with peers or teachers. (c) "Angger-angger lakonan" (patience and resilience): Advocating a patient, resilient, and composed approach to handling various challenges and issues. This research contributes to the understanding that cultural character plays a significant role in shaping the values and behaviors of individuals.